Evaluation of lightweight concrete mixtures for bridge deck and prestressed bridge girder applications - Grotheer, Sarah Jo (Kansas State University, 2008)
As of 2005, 23% of the bridges in the Kansas infrastructure are classified as structurally deficient or functionally obsolete according to the ASCE Infrastructure Report Card (ASCE, 2008). One alternative to replacing the entire bridge structure is replacing only the superstructure with lightweight concrete. This option is more economical for city, county, and state governments alike. Replacing the superstructure with lightweight concrete can oftentimes allow the bridge rating to be upgraded to higher load capacities or higher traffic volumes. Furthermore, lightweight concrete can be used initially in a bridge deck to provide reduced weight and a lower modulus of elasticity, therefore lower cracking potential. The Kansas Department of Transportation is interested in the potential benefits of using lightweight aggregate concrete in Kansas bridge decks and prestressed bridge girders. This research project used three types of lightweight aggregate to develop lightweight concrete mixtures for a bridge deck and for prestressed bridge girders. Two of the lightweight aggregates were expanded shale obtained locally from the Buildex Company. One deposit was located in Marquette, Kansas, and the other in New Market, Missouri. The third lightweight aggregate source was expanded slate obtained from the Stalite Company in North Carolina. Aggregate properties including absorption, gradation, and L.A. Abrasion were evaluated. Over 150 lightweight concrete mixtures were created and tested and several mix design variables such as water-to-cement ratio, cement content, and coarse-to-fine aggregate ratio were evaluated. From these results, optimized bridge deck and optimized prestressed concrete mixtures were developed for each type of lightweight aggregate. Special concerns for lightweight aggregate concrete are addressed. These optimized concrete mixtures were then tested for KDOT acceptability standards for the concrete properties of compressive strength, tensile strength, modulus of elasticity, freeze-thaw resistance, permeability, alkali-silica reactivity, drying shrinkage, and autogenous shrinkage. All concrete mixtures performed satisfactorily according to KDOT standards. In addition, an internal curing effect due to the moisture content of the lightweight aggregate was observed during the autogenous shrinkage test.
Keywords: concrete; lightweight concrete; aggregate; lightweight aggregate; absorption; Engineering, Civil (0543)